ADAT BAGITO - Juswandi, Juswandi (JURNAL PUSTAKA BUDAYA, 2016)
AbstrakDi Kabupaten Kuantan Singingi tepatnya Kecamatan Kuantan Hilir Seberang (KHS), merupakan Kecamatan baru pemekaran dari Kecamatan Kuantan Hilir Baserah, sekarang berdiri sendiri yang bernamaÂ  Kecamatan Hilir Seberang di Kecamatan inilah masih banyak tersimpan berbagai bentuk budaya dan tradisi, salah satunyaÂ  âBagitoâ itu ada. Bagito artinya menerima seseorang yang datang dari daerah lain untuk mengaku sebagai keluargaÂ  sendiriÂ  (mengambil dunsanak) baik diri sendiri mapun keluarga, maka di anggaplah sebagai saudara kandung. Dengan adanya Bagito maka bertambahlah sanak saudatanya semua yang ada dalam suku tempat ia bergabung âBagitoâ Kata Kunci: Adat Bagito.AbstractIn the regency of Kuantan Singingi, there is a district name Kuantan Hilir Seberang. This district has separed from district of Kuantan Hilir Baserah and now it becomes new district. In this district, there is âBagitoâ tradition which still exists and practices by people. âBagitoâ mean receiving someone from different areas to be their own relatives.Â  The person is confessted to be sibling. By having âBagitoâ, the number of family becomes wider. The method used in the research is descriptive by using qualitative approach. The technique used in the research is interview in reader to get real information about the data. The result of the research shown that âBagitoâ tradition may strengthen (friendship) all members in a big family. This tradition also can show them where is their origin family and where is âBagitoâ, but all of them unite in the family.Keywords: Bagito tradition, Kuantan Hilir Seberang, family